2013
DOI: 10.1148/radiol.13122577
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Edema in Vertebral Compression Fractures: Detection with Dual-Energy CT

Abstract: Purpose:To assess the use of the dual-energy computed tomographic (CT) virtual noncalcium technique in the evaluation of bone marrow edema in vertebral compression fractures. Materials and Methods:This prospective study was approved by the institutional review board; informed consent was obtained from all patients. Sixty-three consecutive patients with 112 thoracic and/or lumbar vertebral compression fractures were studied between January 2011 and April 2012. All patients underwent both dual-energy CT (100 kV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
86
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 157 publications
(95 citation statements)
references
References 30 publications
3
86
2
1
Order By: Relevance
“…Currently, only a few studies have reported on the use of DSCT to visualize the bone marrow. 1,5,11,23,29 The attenuation values measured on the non-calcium images obtained by DSCT were higher in abnormal bone marrow areas than in normal areas. These increased attenuation values are correlated with the knowledge about the increase in fluid and/or blood components of the bone marrow in trauma patients.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Currently, only a few studies have reported on the use of DSCT to visualize the bone marrow. 1,5,11,23,29 The attenuation values measured on the non-calcium images obtained by DSCT were higher in abnormal bone marrow areas than in normal areas. These increased attenuation values are correlated with the knowledge about the increase in fluid and/or blood components of the bone marrow in trauma patients.…”
Section: Discussionmentioning
confidence: 90%
“…These increased attenuation values are correlated with the knowledge about the increase in fluid and/or blood components of the bone marrow in trauma patients. 5,30,31 However, the attenuation difference between abnormal and normal bone marrow is greater in elderly patients owing to the increased fat component of their vertebrae. 5 The three false-negative findings were in the vertebral bodies with sclerosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations